2020
DOI: 10.1128/mbio.01865-20
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecies Signaling between Common Variants of Pseudomonas aeruginosa Increases Production of Quorum-Sensing-Controlled Virulence Factors

Abstract: The opportunistic pathogen Pseudomonas aeruginosa damages hosts through the production of diverse secreted products, many of which are regulated by quorum sensing (QS). The lasR gene, which encodes a central QS regulator, is frequently mutated in clinical isolates from chronic infections, and loss of LasR function (LasR−) generally impairs the activity of downstream QS regulators RhlR and PqsR. We found that in cocultures containing LasR+ and LasR− strains, LasR− strains hyperproduce the RhlR/RhlI-regulated an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
74
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 98 publications
16
74
2
Order By: Relevance
“…Extracellular citrate has been detected in S. aureus cultures previously (90,91), and our work shows that this staphylococcal secreted metabolite can be sensed by P. aeruginosa, thus defining another cooperative interaction between these two coinfecting pathogens. Higher concentrations of citrate affect quorum sensing and biofilm formation, and mediate iron uptake in P. aeruginosa (60,92,93). While citrate did not affect iron pathways in our study at the concentration found in S. aureus JE2 supernatant (Table S13), it is possible that higher concentrations that facilitate iron uptake may exist in communities with these two species.…”
Section: S6 and Tablecontrasting
confidence: 53%
“…Extracellular citrate has been detected in S. aureus cultures previously (90,91), and our work shows that this staphylococcal secreted metabolite can be sensed by P. aeruginosa, thus defining another cooperative interaction between these two coinfecting pathogens. Higher concentrations of citrate affect quorum sensing and biofilm formation, and mediate iron uptake in P. aeruginosa (60,92,93). While citrate did not affect iron pathways in our study at the concentration found in S. aureus JE2 supernatant (Table S13), it is possible that higher concentrations that facilitate iron uptake may exist in communities with these two species.…”
Section: S6 and Tablecontrasting
confidence: 53%
“…Another study on the evolution of P. aeruginosa in Caenorhabditis elegans also identified that virulence evolution was mediated by the production of secreted molecules and that attenuation in pathogenicity could be attributed to cheats exploiting the goods produced by cooperators [76]. Taken together, this highlights the importance of social interactions during chronic infection, and that heterogeneous populations likely result in complex interactions that can impact overall community function [77,84]. Future work in this area could focus on exploring genetic diversity in infections using deep sequencing, which may provide insights as to how allelic polymorphism and genetic heterogeneity impacts community function and the outcome of virulence [77].…”
Section: Discussionmentioning
confidence: 93%
“…While LasR-strains are common in CF infections, virulence factors regulated by LasR such as zinc metalloproteases are still reported to be abundant in CF sputum (57). Recent work by Mould et al showed that when LasR+ and LasR-strains were cocultured, the LasR+ strain increased production of RhlR-controlled virulence factors by the LasR-strain (69). Interestingly, LasB and LasA are reportedly regulated by both the LasR and RhlR QS regulators (35).…”
Section: Discussionmentioning
confidence: 99%